Pengaruh Intensitas Modal, Ukuran Perusahaan, dan Sales Growth Terhadap Agresivitas Pajak - Ika Fadhilah Putri; Ratih Qadarti Anjilni (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This research aims to examine the influence of capital intensity, company size, and sales growth on tax aggressiveness. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Panel Data Regression Analysis using the Eviews version 13 application and Microsoft Excel. The population used in this research is Energy Companies Listed on the Indonesia Stock Exchange (BEI) for the 2018-2023 period. The data collection technique in this research is a purposive sampling technique with a population of 87 companies becoming the final 10 company samples or 60 observation data processed in this research. The research results show that simultaneously capital intensity, company size and sales growth influence tax aggressiveness. Partially, capital intensity and sales growth have no effect on tax aggressiveness. Meanwhile, company size influences tax aggressiveness.